An overview on silica aerogels synthesis and different mechanical reinforcing strategies - Maleki, Hajar; Durães, Luisa; Portugal, António (Journal of non-crystalline solids, 2014)
Silica aerogels are lightweight and highly porous materials, with a three-dimensional network of silica particles, which are obtained by extracting the liquid phase of silica gels under supercritical conditions. Due to their outstanding characteristics, such as extremely low thermal conductivity, low density, high porosity and high specific surface area, they have found excellent potential application for thermal insulation systems in aeronautical/aerospace and earthly domains, for environment clean up and protection, heat storage devices, transparent windows systems, thickening agents in paints, etc. However, native silica aerogels are fragile and sensitive at relatively low stresses, which limit their application. More durable aerogels, with higher strength and stiffness, can be obtained by proper selection of the silane precursors, and constructing the silica inorganic networks by compounding them with different organic polymers or different fiber networks. Recent studies showed that adding flexible organic polymers to the hydroxyl groups on the silica gel surface would be an effective mechanical reinforcing method of silica aerogels. More versatile polymer reinforcement approach can be readily achieved if proper functional groups are introduced on the surface of silica aerogels and then co-polymerized with appropriate organic monomers. The mechanical reinforced silica aerogels, with their very open texture, can be an outstanding thermal insulator material for different industrial and aerospace applications. This paper presents a review of the literature on the methods for mechanical reinforcing of silica aerogels and discusses the recent achievements in improving the strength and elastic response of native silica aerogels along with cost effectiveness of each methodology. •Overview on chemistry and synthesis/drying methods of silica aerogels is given.•Literature survey on methods for structural reinforcement of silica aerogels•Literature survey on strategies for silica aerogels reinforcement with polymers•Mechanical reinforcement of silica aerogels by incorporation of fibers is described.